The Effect of Weight Training, Leg Power, on the 50M Freestyle Swimming Speed of Semarang PSC Athletes - Irawan, Fredi; Rahayu, Setya; Rumini, Rumini (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
Swimming fins with various innovative shapes have been designed, among which is the use of swimming fins that has become popular, while the influence of the characteristics of the fins on swimming performance is still being debated. The purpose of this study was to analyze the effect of weight training using long fins, short fins and leg power on the 50 meter freestyle swimming speed of Semarang PSC athletes. This experimental study used a 2x2 factorial design, the research sample of 20 athletes was taken by purposive sampling. Data analysis used Analysis of Variance (ANOVA). The results of the study shows the difference in the effect of weight training with long fins and short fins on the speed of 50 meters crawl style swimming Fcount 4.637> Ftable 4.494, the difference in the effect of high and low leg power on the speed of 50 meters crawl style swimming Fcount 15,973> F table 4,494, interaction of weight training methods and leg power on speed of 50 meters crawl style swimming Fcount 8,780> F table 4,494. The conclusion proved that the long fins weight training method gave better results than the short fins. The speed of 50 meters crawl style swimming in the high leg power group was better than the low leg power group, the long fins weight training method in the high leg power group was better than the low leg power group.